LAAMIYAT AL-ARAB: A GENETIC STRUCTURAL ANALYSIS - Iffat Maimunah; Wildana Wargadinata; M. Faisol; Ribut Wahyudi; Miftahul Huda (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Laamiyat al-Arab is a great literary work that was written during the Jahili Arabs, and received great attention from writers and linguists. However, the aspects of the values it contains and its relation to the social context that underlies Laamiyat al-Arabs’ work are not well-documented. Through Goldmann's genetic structuralism approach, the authors reveal the values, characters, and the internal and external factors generating the Laamiyat al-Arab literature. The results show that the lower class of Jahili Arab community, despite their life’s hardship and distress, could deliver noble values and characters of the marginalized people of its time. Further studies are of great necessity to investigate the contents of literary works other than Laamiyat al-Arab to get an actual picture of Jahili Arabs’ literature.